2018
DOI: 10.1055/s-0038-1667340
|View full text |Cite
|
Sign up to set email alerts
|

Robson Classification System Applied to Induction of Labor

Abstract: Transcervical Foley catheter induction was associated with a higher rate of CS, probably because it was the preferred method used in group 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…had a population size of 1.46%, and the cesarean section rate of the group was 33.02%. Vargas et al (14) found the rate as 8.4 % in this group. However, the previous cesarean was not included in this study, and this rate was relatively high.…”
Section: Discussionmentioning
confidence: 46%
“…had a population size of 1.46%, and the cesarean section rate of the group was 33.02%. Vargas et al (14) found the rate as 8.4 % in this group. However, the previous cesarean was not included in this study, and this rate was relatively high.…”
Section: Discussionmentioning
confidence: 46%
“…According to studies available in the literature, induction failure rates range from 23.4 to 33.8%. 19 20 The present study recorded the following induction failure rates: 42.5% for multiparous women and 58.5% for primiparous women, which corresponded to the 4 th largest cesarean section age. 21 22 Since the HUSM is a regional reference for high-risk deliveries – including prematurity and maternal pathology cases –, the large number of induced delivery failures in this hospital has an impact on cesarean section rates.…”
Section: Discussionmentioning
confidence: 53%
“…[13][14] For example, a study in Lisbon showed that cesarean rates can be reduced to approximately 20% when labor induction is attempted in a proper, monitored manner and in a safe environment. 15 When the results between general births and cesarean sections were compared between Brazilians and foreigners, differences between nationalities were found (possibly due to differences in prenatal services), and the analyses were significant for groups 6 and 8. Other studies also highlighted that women with breech, transverse and multiple gestations, belonging to groups 6, 9 and 8, respectively, have more chances of evolving to surgical delivery.…”
Section: Discussionmentioning
confidence: 95%